Building Customer Satisfaction through Product Quality and Trust: The Role of Customer Motivation - Rizky Abdul Fattah; Rindika Pramadanti (Universitas Sumatera Barat, 2026)
This study aims to examine the effect of product quality and trust on customer satisfaction, both directly and indirectly through customer motivation, among Kopi Tuku consumers. Primary data were collected from 210 respondents selected using purposive sampling and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 3.0. The results indicate that product quality positively influences both customer motivation and satisfaction, while trust also significantly enhances motivation and satisfaction. Customer motivation was found to mediate the relationship between product quality and trust on satisfaction, strengthening their impact. These findings highlight the importance of maintaining product quality and building customer trust to improve experience and loyalty. Practically, this study provides insights for Kopi Tuku management in developing strategies to enhance customer satisfaction. Future research is recommended to include additional factors such as price, promotions, and store atmosphere to gain a more comprehensive understanding of customer motivation and satisfaction.